Mitigating inflammation and fibrosis: the therapeutic potential of quercetin liposomes in COPD - Yin, Changfeng; Tian, Yushan; Yan, An; Wang, Hongjuan; Lu, Fengjun; Li, Xianmei; Li, Xiao; Han, Shulei; Miao, Ruijuan; Chen, Huan; Li, Di; Hou, Hongwei; et al. (Frontiers in Pharmacology, 2024)
IntroductionChronic obstructive pulmonary disease (COPD) is a disease with severe therapeutic obstacles and high worldwide death rate. COPD progresses predominantly through inflammatory response followed by fibrotic destruction. Quercetin (Que), recognized for its anti-inflammatory effects, presents significant promise as a therapeutic candidate for COPD therapy. However, poor water solubility and low bioavailability of Que hinder its further clinical application. Liposomes are renowned for their unique structure and function, which provided an efficient approach for the delivery of Que in various drug delivery systems. This study was aim to prepare a novel Que liposome (Que-lipo) and administrated via intratracheal (i.t.) with cigarette smoke induced COPD mice. The underlying therapeutic mechanisms against lung damage of Que-lipo were explored.MethodsQue-lipo were prepared based on thin film dispersion method and administrated via intratracheal administration. The cigarette smoke induced COPD mice were established and a comprehensive approach was employed to explore the inflammation, pulmonary function and histopathology of lung after i.t. administration of Que-lipo, including enzyme-linked immunosorbent assay, histopathology and immunohistochemistry, reverse transcription-quantitative polymerase chain reaction.Results and discussionQue-lipo not only improved the solubility and biocompatibility of Que but also demonstrated effective cellular uptake in vitro. The inflammation, pulmonary function and pathological condition of lung were improved after i.t. administration of Que-lipo. Que-lipo also regulated the expression of key apoptosis-associated proteins such as Bcl-2 and caspase-3/7, leading to significant inhibition of apoptotic activity in COPD. Furthermore, Que-lipo markedly enhanced its ability to alleviate lung inflammation and fibrosis symptoms by modulating inflammation-related factors and fibrosis signaling molecules. The potential mechanisms of Que-lipo in treating COPD were elucidated, including the suppression of the NLRP3/IL-1β inflammasome pathway and the TGF-β1-related fibrosis signaling pathway.